Fatores clínicos e antropométricos associados à adesão à contagem de carboidratos por pessoas com diabetes mellitus tipo 1 - CAMARA, Lediane Nunes (2023)
Introduction: Type 1 Diabetes Mellitus (T1DM) is an autoimmune disease identified by the failure to produce insulin due to the destruction of pancreatic β cells, resulting from the interaction of various environmental and genetic factors. Nutritional therapy is the most important tool for successful treatment of patients with T1DM, contributing to glycemic control and supplying the energy and nutritional needs of individuals. Thus, the Carbohydrate Counting (CC) is a nutritional strategy that is based on estimating the grams of carbohydrates that will be ingested at each meal, enabling the knowledge of the effects on blood glucose. Some studies show the beneficial relationship between adherence to CC and clinical and anthropometric data in people with T1DM, but Brazilian studies evaluating the relationship between clinical and anthropometric measures and CC for people with T1DM are still scarce. Aim: To verify the association between the clinical and anthropometric profile and adherence to CC by people with T1DM. Methodology: This is a cross-sectional, descriptive and analytical study carried out with adults with T1DM, of both sexes, who knew the CC strategy. Data were collected through an online form, which contained questions regarding knowledge of CC and clinical and anthropometric data. For data analysis, the Statistical Package for Social Science software, version 24.0, was used, with descriptive data categorized into absolute frequency and proportion, and in the analytical phase, Pearson's Chi-Square test, with residual analysis. A statistical significance level of p<0.05 was considered. Results: A total of 188 people with T1DM were evaluated, most of them with a diagnosis time of more than 10 years (n=120; 63.8%), eutrophic (n=105; 55.9%) and with a mean BMI of 25.0 ±4, 5 kg/m2, had increased HbA1c (n=104; 55.3%) and had CC (n=105; 55.9%). There was an association between adherence to the CC and having been tested for HbA1c for up to 3 months (p=0.037), adequate HbA1c (p=0.017), having more than 10 years of T1DM diagnosis (p=0.002) and between adequate HbA1c and performing of CC at lunch (p=0.034) and dinner (p=0.019), using CC applications (p=0.001) and non-specific CC applications (p<0.001), as a way of researching the amount of carbohydrates. Conclusion: After carrying out this study, it is concluded that not performing CC may be associated with obesity, adherence to CC is associated with better glycemic control, with the measurement of HbA1c at the correct time and seems to be higher over the time of diagnosis , as well as the use of cell phone applications seems to help in adherence to this nutritional therapy strategy. Thus, the study was fundamental, as it appears that adherence to CC is a nutritional strategy of extreme importance in maintaining adequate clinical and anthropometric characteristics during the treatment of DM1.